Isyarat Ilmiah Sidik Jari dalam al-Qur’an: Analisis Saintifik Surah Yasin 36:65, al-Qiyamah 74:4 dan al-Anfal 8:12 - Agus Widianto; Ridwan; Onrico Candra; Farid Fauzi; Zulfirki (Kartika: Jurnal Studi Keislaman, 2025)
The research aims to explore how classical and contemporary exegetes interpret verses related to bodily testimony in the Hereafter and to analyze the extent to which these interpretations align with scientific findings in modern biometrics. This study employs a qualitative library research method by analyzing primary sources from classical, medieval, and contemporary tafsir literature, supported by secondary scientific references on fingerprint physiology and identity verification. The findings indicate that classical scholars generally interpret banānah as a reference to the reconstruction of human bodily structures on the Day of Resurrection, emphasizing divine power in restoring even the smallest parts of the body. In contrast, contemporary interpretations increasingly highlight the uniqueness of fingerprints as a form of individual identity, suggesting a possible scientific dimension in the verse. This demonstrates that the Qur’anic reference to banānah may encompass both theological meaning and indicators of biological specificity. The study contributes an integrative perspective that bridges traditional exegesis with modern scientific insights, offering a more comprehensive understanding of the verse in light of interdisciplinary approaches.